The Suitability of Propolis as a Bioactive Component of Biomaterials - Lesmana, Ronny; Zulhendri, Felix; Fearnley, James; Irsyam, Ilham A.; Rasyid, Renaldi P. H. N.; Abidin, Trimurni; Abdulah, Rizky; Suwantika, Auliya; Paradkar, Anant; Budiman, Arief S.; Pasang, Timotius (Frontiers in Pharmacology, 2022)
Propolis is a resinous product collected by bees from plant exudates to protect and maintain hive homeostasis. Propolis has been used therapeutically for centuries as folk medicine. Modern research investigating the diversity of the chemical composition and plant sources, biological activity, extraction processes, analytical methods, and therapeutic properties in clinical settings have been carried out extensively since the 1980s. Due to its antimicrobial, anti-inflammatory, and immuno-modulator properties, propolis appears to be a suitable bioactive component to be incorporated into biomaterials. This review article attempts to analyze the potential application of propolis as a biomaterial component from the available experimental evidence in the literature. The efficacy and compabitility of propolis depend upon factors, such as types of extracts and types of biomaterials. Generally, propolis appears to be compatible with hydroxyapatite/ calcium phosphate-based biomaterials. Propolis enhances the antimicrobial properties of the resulting composite materials while improving the physicochemical properties. Furthermore, propolis is also compatible with wound/skin dressing biomaterials. Propolis improves the wound healing properties of the biomaterials with no negative effects on the physicochemical properties of the composite biomaterials. However, the effect of propolis on the glass-based biomaterials cannot be generalized. Depending on the concentration, types of extract, and geographical sources of the propolis, the effect on the glass biomaterials can either be an improvement or detrimental in terms of mechanical properties such as compressive strength and shear bond strength. In conclusion, two of the more consistent impacts of propolis across these different types of biomaterials are the enhancement of the antimicrobial and the immune-modulator/anti-inflammatory properties resulting from the combination of propolis and the biomaterials.